Gambaran Lama Rawat Inap Pasien Pneumonia Balita Berdasarkan Jenis Terapi Antibiotik di Rumah Sakit X Jakarta - Lathvi Masyithah; Erischa Putri Diana; Dona Suzana (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
Pneumonia is one of the leading causes of morbidity and mortality in infants in Indonesia. Antibiotic therapy is a key component of its treatment. However, the choice between single antibiotic therapy and combination therapy remains a subject of debate, particularly in relation to efficiency and length of hospital stay. This study aims to compare the length of hospital stay in infants with pneumonia who received single antibiotic therapy and combination antibiotic therapy at Hospital X. The study employs a quantitative observational design with a retrospective approach. Data were collected from medical records of pediatric pneumonia patients during a specific period at Hospital X, with 44 patients receiving single antibiotic therapy and 6 patients receiving combination therapy. Data analysis was performed using the non-parametric Mann–Whitney test to compare hospitalization duration between the two therapy groups. The results of the Mann–Whitney test showed no significant difference in the length of hospital stay between patients receiving monotherapy and combination therapy (p = 0.214; p ≥ 0.05). This indicates that monotherapy provides clinically comparable outcomes to combination therapy in terms of length of hospital stay. Single antibiotic therapy was found to be comparable in effectiveness to combination therapy in terms of length of hospital stay in infants with pneumonia. These results support the application of rational antibiotic therapy principles and provide a basis for the efficient use of antibiotics.